The role of CEO’s overconfidence and gender diversity in top management teams in firm performance - Matos, André Dantas (2018)
This thesis focuses on leader’s overconfidence and their influence on firm performance, measured by the ROA. Overconfidence may bias several decisions inside companies, namely the risk component that ought to be undertaken by the CEO and Top Management Team. The data was collected through the analysis of the letters to the shareholders presented in the annual reports, namely word counting related to different personality traits. Letters from 2008 to 2016 were gathered, in a total of 1162 letters from 148 companies and 350 CEOs from different industries. The second dimension studied was gender diversity in the top management team and the overconfidence of the CEO. Women in general are considered more risk averse than men in the literature, which could mean a negative influence on the relationship between overconfidence and performance. However, since it was not found a significant relationship, this supports the idea that businesswomen have not significant differences comparing to men considering overconfidence and risk. Finally, a positive relationship was found between gender, the proportion of women in the top management team and financial performance. In the robustness tests 37 regressions were computed to support my facts and, in the end, limitations and future research opportunities were presented and discussed.